2010
DOI: 10.3390/molecules15042845
|View full text |Cite
|
Sign up to set email alerts
|

Cell Proliferation of HaCaT Keratinocytes on Collagen Films Modified by Argon Plasma Treatment

Abstract: Argon plasma treatment was used to modify the surface of atelocollagen films using a plasmochemical reactor. To evaluate the effects of the treatment, the untreated and treated samples were characterized by Attenuated Total Reflectance Fourier Transform Infrared Spectroscopy (ATR-FTIR), Scanning Electron Microscopy (SEM) imaging, and X-ray Photoelectron Spectroscopy (XPS) techniques. Cell growth was carried out by culturing human immortalized keratinocyte (HaCaT) cells and proliferation was measured via MTT as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 56 publications
4
51
0
3
Order By: Relevance
“…During plasma cleaning, contaminants are volatized and removed, while the bulk properties of the substrate remain unaffected. Argon is by far the most common noble gas used in plasma treatment because of its high ablation efficiency, chemical inertness with the surface material, and relatively low cost [37].…”
Section: Surface Cleaningmentioning
confidence: 99%
“…During plasma cleaning, contaminants are volatized and removed, while the bulk properties of the substrate remain unaffected. Argon is by far the most common noble gas used in plasma treatment because of its high ablation efficiency, chemical inertness with the surface material, and relatively low cost [37].…”
Section: Surface Cleaningmentioning
confidence: 99%
“…It has been shown that such modifications of polymer surface have a significant influence on the mechanisms of cell growth and adhesion. [28][29][30][31][32][33][34] Wei et al [35] used oxygen plasma to create different wettabilities on hexamethyldisiloxane (HMDSO). Their results showed that hydrophilic surfaces increased initial attachment of osteoblast cells.…”
Section: Introductionmentioning
confidence: 99%
“…Buna bağlı olarak yapılan diğer çalışmalarda olduğu gibi soğuk plazma uygulamasının hücre canlılığını ve çoğalmasını olumsuz yönde etkilemediği gösterildi [16].…”
Section: Tartışma Ve Sonuçunclassified